Design of the University Mobile Educational Environment - V. I. Toktarova; A. E. Shpak (Высшее образование в России)
The article addresses issues related to the description of the aspects of the instructional design of a mobile educational environment of a modern higher education institution. The authors give the definitions of the mobile educational environment, describe its functional features, and also consider the requirements for its instructional design and development. The article presents the clustering of digital services for the full implementation of a mobile educational environment (services for planning and supporting educational activities, services for organizing and supporting educational activities, communication and feedback services, general information services). The results of the experimental research to identify the attitude of students, teachers and administrative workers to the functional significance of mobile technologies and their application in the educational process are presented.